ANALISIS KESALAHAN GRAMATIKAL BAHASA JERMAN TULIS - NOVITA R, INDAH (LATERNE, 2014)
Language has an important role in human life. The use of bilingual language use can lead to chaos, better known as interference. This is what causes the error to speak. Error analysis is a procedure commonly used by working writers with a language teacher, through the leverage of data, identification of errors contained in the data, explanation of the error, the classification error based on the cause, and the evaluation or assessment of the level of seriousness of the error. For that reason, the researchers chose to study "Analysis of Causes Errors In Writing Essays grammatical description IPS Class XI students of SMA Negeri 2 Kediri 3 school year 2012/2013" The problem is that cold researched any grammatical errors in essay form description of German-speaking high school students do?, And what are the causes of errors in the description of the arrangements made German-speaking high school students?. The method used is descriptive qualitative research. Research subject is class XI IPS 2 SMA Negeri 3 Kediri. The technique of collecting data through student essays made. The results of the analysis showed that there were some errors on the results of the students' fault that orthogarfi, morphosyntax, and leksikosemantik. Of the 106 mistakes there are 19 students make mistakes orthography, morphosyntax 30 students make mistakes, and make mistakes leksikosemantik 58 students. As for the cause of mistakes made by students because of errors across languages ??and intralanguage. Keywords:writing skill and grammatics